Efektivitas Edukasi Gizi terhadap Kepatuhan Diet dan Sisa Makanan Pasien Diabetes Melitus di RS Muhammadiyah Gresik - Melani Putria Yudismara; Amalia Rahma (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Diabetes Mellitus (DM) is a chronic disease with a high prevalence in Indonesia that requires appropriate dietary management to prevent complications. Nutrition education plays a crucial role not only in improving patient knowledge but also in influencing eating behavior and dietary compliance. This study aims to analyze the effectiveness of nutrition education on dietary compliance and food waste among hospitalized DM patients at Muhammadiyah Hospital Gresik. This pre-experimental research used a one-group pretest–posttest design involving 20 respondents selected through purposive sampling. The independent variable was nutrition education in the form of counseling, leaflets, and direct guidance, while the dependent variables were dietary compliance and food waste, measured using observation and the food weighing method with a scoring system of 0–25–50–75–100%. The results showed a significant increase in dietary compliance from 30% to 75% and a decrease in food waste from 65% to 20% after education (p < 0.05). Thus, nutrition education effectively improves dietary adherence and reduces food waste among DM patients.